2005
DOI: 10.3346/jkms.2005.20.5.816
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotype C Prevails Among Chronic Carriers of the Virus in Korea

Abstract: Hepatitis B virus (HBV) is one of the major causative agents of chronic liver diseases in Korea. HBV has been classified into 8 genotypes by a divergence of >8% in the entire genomic sequence, and have distinct geographic distributions. There are limited data on the relevance between HBV genotypes and clinical outcomes in Korea. To investigate the clinical feature relating to HBV genotype in Korea, a total 120 serum samples with HBsAg (65 from Seoul and 55 from the other city in Korea) were obtained from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 36 publications
1
85
0
Order By: Relevance
“…1,5 Verschuere et al 23 report that the predominant subtypes in Europe are genotypes A and D. This is true also for Portugal, especially in the Northern region of the country. 14,15 In countries where endemicity is low, and in age groups not covered by mandatory vaccination, sexual transmission is more common among males, whereas intrafamilial transmission seems to predominate among females.…”
Section: Introductionmentioning
confidence: 97%
“…1,5 Verschuere et al 23 report that the predominant subtypes in Europe are genotypes A and D. This is true also for Portugal, especially in the Northern region of the country. 14,15 In countries where endemicity is low, and in age groups not covered by mandatory vaccination, sexual transmission is more common among males, whereas intrafamilial transmission seems to predominate among females.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, HBeAg loss or seroconversion rate was very low (2.6%) during the observational period compared with previous studies. This result might be due to long-standing infection of HBV by vertical transmission and a particular pattern of HBV genotype (genotype C) in Korea even though we did not analyze the genotype [26] . In this study, virologic breakthrough was not observed, and ten patients did not show complete virologic response during the treatment with TDF.…”
Section: Conflicts Of Interestmentioning
confidence: 97%
“…HBV genotypes, HBV DNA and Alanine transaminase (ALT) levels are regarded as important factors influencing HBV clearance and the development of HCC. However, HBV genotype C predominates among CCs of the virus in Korea (39)(40)(41)(42)(43), and the levels of HBV DNA and ALT were found to fluctuate during the follow-up for the majority of our HBV cohort. Therefore, logistic models for HBV clearance were adjusted only for age and sex.…”
Section: Statisticsmentioning
confidence: 99%